An IPA assessment of international guests’ perceptions on hotel service operations / Anderson Ngelambong…[et al.] - Anderson, Ngelambong; Isa, Nina Farisha; Mohd Hanafiah, Mohd Hafiz; Kibat, Silverina Anabelle (Faculty of Hotel and Tourism Management, Institut Teknologi MARA, Selangor, Puncak Alam Campus, 2011)
The purpose of this paper is to examine international guests’ perceptions on the importance and performance of eight key areas of hotel operation. From in depth review of the literature, eight attributes of hotel operation were identified namely accommodation services, resort day activities, dining services, bar/lounge, night entertainment, airport transfers, check-in/out, and in-house service. The findings of the study are imperative to provide valuable information for hotel managements to improve their operation performance and guests’ satisfaction. Also, the results may present useful facts with regards to potential future expansion or reduction/removal in hotel operation services. The study was conducted at Batu Feringghi, Pulau Pinang with the participation of international guests at five hotels. A total of 110 questionnaires were returned from 150 distributed to the respondents who stay at the hotels. Due to missing values and alike, the sample was further reduced to 104 respondents representing a total rate of 69.33 per cent. An Importance Performance Analysis (IPA) technique was used to determine the importance guests assign to salient attributes and to assess their satisfaction with the hotels performance on each of the attributes. A mean statistic for each item was generated by using Excel Database before being plotted to the IPA grid presentation. The study found that among the eight attributes of the hotel operation bar/lounge was rated as the least importance. While in terms of guests’ satisfaction, night entertainment received the lowest mean ratings.